THE IMPLEMENTATION OF ENGLISH-ONLY POLICY IN THE TERTIARY EFL CONTEXT IN TAIWAN - Wei, David Dirkwen (Universitas Pendidikan Indonesia, 2013)
Abstract: The implementation of English-only policy in the English classes at Wenzao Ursuline College of Languages in Taiwan has continued for nearly 40 years. Its advantages and disadvantages have also been debated and challenged because of the rising demands on students’ English proficiency in Taiwan. This study intended to reexamine the efficiency of the implementation of English-only policy in the English learning at a college of languages in Taiwan. Both quantitative and qualitative methods were used in the process of data collection. 279 English major and non-English major students were invited to answer questionnaires, and six participants were invited to join interviews. The process of data analysis included the analysis of both the quantitative questionnaire data and the qualitative interview data. This study found students’ progress in English listening and speaking proficiency in the basic and lower-intermediate levels because of English-only policy. However, the interaction between teachers and some students was hampered because of the policy. Also, the ambiguity emerging in the insistence on using English only blocked some learners from comprehending the meanings of the texts they were learning, specifically the texts in the upper-intermediate and intermediate-advanced levels of English reading and writing courses. This study also found that proper tolerance of using both students’ native language and English in TEFL classes in the way of code-switching may help students more than the implementation of English-only policy in a tertiary TEFL context.